The Paradox of Interactive Media: The Potential for Video Games and Virtual Reality as Tools for Violence Prevention - Bowman, Nicholas David; Ahn, Sun Joo; Mercer Kollar, Laura M. (Frontiers in Communication, 2020)
Interactive media such as video games and virtual reality (VR) provide users with lived experiences that may be dangerous or even impossible in daily life. By providing interactive experiences in highly authentic, detail-rich contexts, these technologies have demonstrated measurable success in impacting how people think, feel, and behave in the physical world. At the same time, violent interactive media content has been historically connected with a range of antisocial effects in both popular press and academic research. Extant literature has established a small-but-statistically significant effect of interactive media violence on aggressive thoughts and behaviors, which could serve as a risk factor for interpersonal violence. However, left unexplored is the seemingly paradoxical claim that under some conditions, interactive media experiences might protect against interpersonal violence. Drawing on advances in media theory and research and the evolution of interactive media content and production practices, the current manuscript suggests ways in which interactive media violence may be leveraged to lower the likelihood of real-world violence experiences. For example, research on both violent and non-violent games has found that players can (a) express guilt after committing violent acts, (b) report reflective and introspective emotional reactions during gameplay, and (c) debate the morality of their actions with others. Regarding VR, studies have demonstrated that (a) witnessing physical violence in immersive spaces led participants to take the perspective of victims and better understand their emotional state and (b) controlled exposure to traumatic or violent events can be used for treatment. Broadly, studies into video games and VR demonstrate that the impact of actions in virtual worlds transfer into the physical worlds to influence (later) attitudes and behaviors. Thus, how these experiences may be potentially harnessed for social change is a compelling and open consideration, as are side-effects of such interventions on vulnerable groups. The current manuscript summarizes emerging research perspectives (as well as their limitations) to offer insight into the potential for interactive media violence to protect against real-world violence victimization and perpetration.